(untitled) (Global Journal of Management and Business Research, 2024)
The current research explores the latent drivers of job satisfaction in Trinidad and Tobago. The aim is to determine the construct validity of the Hackman Oldham (1975) Job Characteristics Model (JCM) to measure job satisfaction. Data was collected from employees using the cross-sectional research method and conveniently sampled from twelve (12) service institutions. The twelve (12) service institutions span three sectors: information and communications technology (ICT), tertiary education, and public utilities. These three (3) sectors were chosen because they represent the three most significant sectors in the Trinidad and Tobago economy and three (3) different levels of industry. Using three (3) different sectors in research enhances generalizability by providing a more diverse sample, reducing the risk of bias, and increasing the likelihood that findings can be applied to a broader range of contexts or populations. The service institutions include TSTT, FLOW, and DIGICEL (Information and Communications Technology).